Antioxidant and Anti-inflammatory in Vitro Activities of Phenolic Compounds from Tropical Highland Blackberry (Rubus adenotrichos) - Azofeifa Cordero, Gabriela (2013)
This study evaluates the antioxidant and anti-inflammatory activities in a polyphenol extract from blackberries. The antioxidant activity measured via oxygen radical absorbance capacity (ORAC) was higher for the blackberry extract (4339 ± 144 μM TE/g) than for quercetin and ellagic acid. The blackberry phenolic compounds protected liposomes and liver homogenates against lipid peroxidation; in both models, the antioxidant activity (IC50 = 7.0 ± 0.5 and 20.3 ± 4.2 μg/mL, respectively) was greater than that found with Trolox. The extract inhibited superoxide production by NADPH oxidase in THP-1 cells and nitrite production in J774A.1 cells stimulated with LPS+IFNγ, with nitrite production decreasing after 4 h of incubation with the extract, mainly through a strong scavenging activity. However, 24 h of treatment reduced the amount of nitrites (IC50 = 45.6 ± 1.2 μg/mL) because of a down-regulation of iNOS protein expression, as demonstrated by Western blotting. The inhibitory activities found in blackberry phenols suggest a potential beneficial effect against oxidative stress and inflammatory processes.